Pengaruh tingkat suku bunga kredit terhadap permintaan kredit usaha produktif Koperasi Credit Union Sauan Sibarrung Kabupaten Tana Toraja - Pagiu, Chrismesi; Pundissing, Rati (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of credit interest rates on the demand for productive business credit of the Sauan Sibarrung Credit Union Cooperative, Tana Toraja Regency. The data analysis method used is descriptive quantitative using a credit report that contains the loan amount based on the credit interest rate at the Sauan Sibarrung CU Cooperative. The analytical technique used is simple linear regression analysis and significance test using the SPSS version 26 program. Based on the results of calculations with the t test on the loan interest rate variable, the results of t count (-2,3) < t table (3.182), so it can be concluded that the loan interest rate variable has no effect on the demand for productive business loans at the Sauan Sibarrung Credit Union Cooperative, Tana Toraja Regency. From the results of the Coefficient of Determination, it shows that 65.2% of the loan interest rate affects the demand for productive business loans while 34.8% is influenced by other variables not included in the study, while the correlation between the interest rate variable and the demand for productive business loans is 0.807, which means strong relationship between variables.